Anthocyanins Absorption of Grapes (Vitis vinifera) on Filter Paper, Whatmann no. 41 and Whatmann no. 42 for Identification of Borax - Kurniawan, Deny; Pramaningsih, Vita; Rusdi, Rusdi; Lesmana, Oktavianti Dwi (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2023)
Borax detection can be done using the flame test method, volumetric titration, spectrophotometric analysis, and qualitatively using natural materials such as curcumin and anthocyanins. Acid-base titrations have the potential to utilize the high content of anthocyanins in grapes as an indicator of natural acid-base. The research objective was to determine the potential of anthocyanins in the flesh and skin of grapes in detecting natural borax, which is absorbed on filter paper, Whatmann paper no. 41, and Whatmann paper no. 42. We then tested it on meatball samples from five vendors in Samarinda Seberang and Mangkupalas village. The research method used is a quantitative analysis of the color changes that occur. Based on the research results, filter paper can have better absorption, as shown by the dark color on Whatman No. 41 and 42. Grape skin extract can detect borax more clearly than flesh by forming a dark purple ring when reacted with borax. In testing using meatball samples, the overall results of the samples contained borax. It was concluded that the filter paper from the absorption of grape skin anthocyanins could be used as an alternative for quantitatively testing the borax content in food.